Docência universitária: de bacharel a professor nos cursos de Ciência da Computação e Sistemas de Informação - Silva, Fernanda Quaresma da (2018)
The research has aimed to analyze the learning of the teaching process of graduate students preparing for teaching at Computer Sciences and Information Systems courses of the Federal University of Uberlândia - UFU. The research problem has been announced such as: how does learning of the teaching process occurs for graduate students in the Computer Sciences and Information Systems courses in UFU? What have been their formative courses and which contributions does formation give to develop their professional identity? What are the main difficulties faced by the teachers of such courses referring to the teaching practice? The exploratory investigation, having a qualitative approach, used as instruments to build data the documental analysis and questionnaires. The main references which guided the research were Melo (2009; 2018); Pimenta; Anastasiou (2014); Almeida (2012); Carvalho (2013); Zabalza (2004), among other ones. Data analysis points that teaching knowledge is mobilized in the teaching practices, even though it is not declared by some of them, with the prevalence of experience expertise, elaborated from formative and professional paths. The professional identity is built from the references of teaching experienced as students. Before the exposed one reaffirms that the learning of teaching of graduate students to be teachers occurs, mainly, in the intersperse of past experience prior to university teaching and teaching knowledge built in the struggles with the pedagogical practice. Concerning the specificity of the teacher´s formation, that is, how students learn to be teachers, it is highlighted that formation is not systematized and, therefore, is still insufficient, mainly by the omission of post-graduation courses (masters and doctorate) by not treating themes related to the pedagogical knowledge. In this sense, one reaffirms the importance of institutional politics of formation and professional development for teachers, which contribute to the empowerment of a University Pedagogy which values the university teaching and the teacher´s expertise.